Buttons to Pearls to Chips or a New Use for Clams - Harold A. Mathiak (Hello World!, 1974)
Another major development is taking place in the utilization of freshwater clams. A new market for clam shells developed in late fall of 1973 when the Tennessee Shell Company started making novelties of crushed and polished bits of shells imbedded in clear plastic.